Experimental investigation of a topology-optimized phase change heat sink optimized for natural convection - See, Yao Song (2022)
In this study, a topology-optimized heat sink is developed and applied to electronics cooling by utilizing a phase change material interspersed through a finned structure. The topology optimization is performed by the minimization of the global thermal compliance in the solution of the modified momentum equation with the Boussinesq approximation to account for natural convection. The optimized heat sink, namely the natural convection topology-optimized heat sink, was fabricated by Selective Laser Melting, a metal additive manufacturing technique. The natural convection topology-optimized heat sink was experimentally characterized based on its base temporal temperature and its operation time. The performance of our newly developed heat sink was then evaluated by comparing against a conventional heat sink design, a baseline design with no surface enhancements, and a second topology-optimized heat sink based on heat conduction. The results show that the natural convection topology-optimized heat sink has a lower base temperature compared to the conventional heat sink, but higher base temperature than the second topology-optimized heat sink during the PCM melting phase. However, the natural convection topology-optimized heat sink has an operation time which is 31.0% longer than all the other heat sinks with enhanced structures. Through visualization of the melting process, we can deduce that the longer operation time of the natural convection topology-optimized heat sink is primarily due to the movement of the melt front which results in a slower melting, while optimizing natural convection of the melted material. These mechanisms maintain a reasonably low heat sink base temperature.